Family Functioning and Moral Reasoning Among Early Adolescence - Salsabila Syahira; Hazhira Qudsyi (Ittishal Educational Research Journal, 2021)
This research aimed to test empirically correlation between family functioning and moral reasoning in early adolescents. This research was carried out on 143 primary high-school students in Balikpapan. This research used a quantitative approach with moral reasoning scale and family functioning scale to measure variables. Result of data analysis showed that there was a significant positive correlation between family functioning and moral reasoning. And for the analysis between family functioning and each dimension of moral reasoning, the results were no correlation between family functioning and pre-conventional moral reasoning, family functioning correlate with conventional moral reasoning, and no correlation between family functioning and post-conventional moral reasoning.